The epidemiology and economic impact of varicella-related hospitalizations in Turkey from 2008 to 2010: a nationwide survey during the pre-vaccine era (VARICOMP study) - Dinleyici, Ener Cagri; Kurugol, Zafer; Turel, Ozden; Hatipoglu, Nevin; Devrim, Ilker; Agin, Hasan; Akarsu, Saadet (Springer, 2012)
Varicella can cause complications that are potentially serious and require hospitalization. Our current understanding of the causes and incidence of varicella-related hospitalization in Turkey is limited and sufficiently accurate epidemiological and economical information is lacking. The aim of this study was to estimate the annual incidence of varicella-related hospitalizations, describe the complications, and estimate the annual mortality and cost of varicella in children. VARICOMP is a multi-center study that was performed to provide epidemiological and economic data on hospitalization for varicella in children between 0 and 15 years of age from October 2008 to September 2010 in Turkey. According to medical records from 27 health care centers in 14 cities (representing 49.3% of the childhood population in Turkey), 824 children (73% previously healthy) were hospitalized for varicella over the 2-year period. Most cases occurred in the spring and early summer months. Most cases were in children under 5 years of age, and 29.5% were in children under 1 year of age. The estimated incidence of varicella-related hospitalization was 5.29-6.89 per 100,000 in all children between 0-15 years of age in Turkey, 21.7 to 28 per 100,000 children under 1 year of age, 9.8-13.8 per 100,000 children under 5 years of age, 3.96-6.52 per 100,000 children between 5 and 10 years of age and 0.42 to 0.71 per 100,000 children between 10 and 15 years of age. Among the 824 children, 212 (25.7%) were hospitalized because of primary varicella infection. The most common complications in children were secondary bacterial infection (23%), neurological (19.1%), and respiratory (17.5%) complications. Secondary bacterial infections (p < 0.001) and neurological complications (p < 0.001) were significantly more common in previously healthy children, whereas hematological complications (p < 0.001) were more commonly observed in children with underlying conditions. The median length of the hospital stay was 6 days, and it was longer in children with underlying conditions (< 0.001). The median cost of hospitalization per patient was $338 and was significantly higher in children with underlying conditions (p < 0.001). The estimated direct annual cost (not including the loss of parental work time and school absence) of varicella-related hospitalization in children under the age of 15 years in Turkey was $856,190 to $1,407,006. According to our estimates, 882 to 1,450 children are hospitalized for varicella each year, reflecting a population-wide occurrence of 466-768 varicella cases per 100,000 children. In conclusion, this study confirms that varicella-related hospitalizations are not uncommon in children, and two thirds of these children are otherwise healthy. The annual cost of hospitalization for varicella reflects only a small part of the overall cost of this disease, as only a very few cases require hospital admission. The incidence of this disease was higher in children < 1 year of age, and there are no prevention strategies for these children other than population-wide vaccination. Universal vaccination is therefore the only realistic option for the prevention of severe complications and deaths. The surveillance of varicella-associated complications is essential for monitoring of the impact of varicella immunization.
Keywords: Varicella; Turkey; Varicella-related hospitalization; Varicella vaccine